Genomic analysis of porcine circovirus type 2 from southern China. Issue 4 (8th June 2020) - Lv, Qizhuang; Wang, Tao; Deng, Jiahua; Chen, Yan; Yan, Qiu; Wang, Daobo; Zhu, Yulin
Abstract: Background: Porcine circovirus type 2 (PCV2) is recognized as virulent porcine pathogen and has been linked to porcine circovirus diseases (PCVD). However, there remain many unknowns regarding the spread and epidemic growth of PCV2. Methods: To assess the genetic diversity of PCV2 in the southern China, a total of 92 sequences of PCV2 strains from this region were retrieved from GenBank and were subjected to amino acid variation and phylogenetic analyses together with 28 representative sequences, based on the sequence of the ORF2 gene, from different swine‐producing countries. Results: All 92 PCV2 strains shared between 93.7% and 100% sequence similarity and could be divided into four genotypes (PCV2a, PCV2b, PCV2d and PCV2h), of which PCV2d had surpassed PCV2b and became the most prevalent PCV2 genotype in this region. Alignment of the deduced amino acid sequences of the capsid protein revealed that the obtained PCV2 strains possess two major heterogenic regions/hypervariable regions (positions 52–68 and 185–191), which were within or close to the epitopic regions in the capsid (Cap) protein. Meanwhile, the 92 PCV2 sequences also show evidence of at least five unique recombination events. Conclusion: The data in this study indicate that the PCV2 strains in the southern China are undergoing constant genetic variation and that the predominant strain and its antigenic epitopes in this area have been gradually changing in recent years. Abstract : PCV2 strains from the Beibu Gulf of China could be divided into four genotypes (PCV2a, PCV2b, PCV2d and PCV2h), of which PCV2d had surpassed PCV2b and became the most prevalent PCV2 genotype in this area. In addition, the Beibu Gulf PCV2 strains possess two major heterogenic regions/hypervariable regions (positions 52–68 and 185–191), which were within or close to the epitopic regions in the capsid (Cap) protein. Meanwhile, these PCV2 sequences also show evidence of at least five unique recombination events.